Assessing land efficiency of biomethane industry: A case study of Sicily. (August 2018) - Selvaggi, Roberta; Pappalardo, Gioacchino; Chinnici, Gaetano; Fabbri, Claudio I.
Abstract: Recent estimates show that the potential for biomethane production in Italy for 2030 is about 8 Bn Nm 3 /year, initially by upgrading the biogas produced by anaerobic digestion. We derive the 'Land Efficiency' of Biomethane in accordance with the Biogasdoneright ® principles in Sicily (Italy), from the standard formula to determine the 'First Crop Land Requirement'. The results were achieved using large proportions of 'integration biomasses'. The concept of Land Efficiency is verified because the first constituent of the formula (land efficiency) is much higher than the second one (biomethane yield of monocrops). The outcome of this study indicates clearly that 'integration biomasses' in the Sicilian context are among those which produce advanced biofuels. All by-products and wastes from the agrifood sector are necessary to produce about 562 million Nm 3 /year of biomethane in Sicily for 2030 (about 8% of the Italian one), allocating only 28, 000 ha for the monocrops for the anaerobic digesters. Highlights: The yearly potential production of BM in Sicily is about 562 million Nm 3, for 2030. Sicily contributes to Italian BM goal producing monocrops only on 2% of its UAA. We derive the 'Land efficiency' of the Biomethane from the formula to determine FCLR. 'Land efficiency' (A/FCLR) is much higher than 'Monocrop yield BM' (C*P).